ESTIMATIONG TECHNICAL EFFICIENCY OF WHEAT FARMS UNDER SUPPLEMENTARY IRRIGATION USING THE STOCHASTIS FRONTIER APPROCH(SAMPLING AREA: TELLKEF DISTRICTL - Salim Al-Niamy; Z. Ahmed (Mesopotamia Journal of Agriculture)
ABSTRACT Wheat production under dry-land farming systems faced sharply seasonal fluctuation caused by variability of whether conditions mainly distribution and quantity of precipitation which affect yield and production . In Tellkef district (research area) . the amount of precipitation reached to 186.5 mm during (2008-2009), beside there was a diminishing in share of available water in irrigation and its poor investment. How ever there was a need for food because of increasing in population . for increasing the efficieny uses and economically water resourses there must be an active irrigation system to use. The aim of thin work was to estimate the technical efficiency (TE) of wheat farms by using stochastic frontier analysis and transcendental logarithmic depending on field data of a random sample contain 53 farms in tellkef district-Nineveh proviance the results revealed a technical efficiency of 62% (medium) and thin means that the impact of in-efficiency represented by the element ui produce the same amount of wheat usin only 62% or less of the input to reach optimum efficiency . however there was a positive relation ship between mechanical technology with seeds, area, and production . mean while production had a negative relationship with labor and quantity of irrigated water. Increasing water irrigation for crop needs by 1% will cause a drope in production by 0.808% which leads a waste of water resources and a decrease in technical efficiency down the optimum degree. .